Corporate Taxation in the Global Economy. (Policy Papers; Policy Paper, 2019)
The policy paper Corporate Taxation in the Global Economy stresses the need to maintain and build on the progress in international cooperation on tax matters that has been achieved in recent years, and in some respects now appears under stress. With special attention to the circumstances of developing countries, the paper identifies and discusses various options currently under discussion for the international tax system to ensure that countries, and in particular low-income countries, can continue to collect corporate tax revenues from multinational activities.